THE ROLE OF TEACHERS IN BUILDING TOGETHERNESS IN MULTICULTURAL AND MULTILINGUAL EDUCATION AT ELEMENTARY SCHOOL - Dedy Suhery; Syarifah Hanim (Proceeding International Seminar of Islamic Studies, 2021)
: The diversity of ethnicities, culture and language in Indonesia is the reality of history and socio-cultural. Concerning the phenomenon, this paper explores some issues on teacher's role in building togetherness in multicultural and multilingual education applied in elementary school. The method used in this study is a qualitative descriptive. And the data will be analyzed by using the Miles and Huberman technique (reduction, display, verification). The research informants were a girl student of the fourth class, teachers, and the headmaster of SDIT Lukmanul Hakim Langsa, Aceh. The findings suggest that the teachers of SDIT Lukmanul Hakim Langsa understood the students' needs, and they were able to build students' togetherness in their class and school environment. From its understanding of multilingual education, it can be found that an Arabic teacher knew the children's needs for the initial stage of multilingual education, especially considering students' ages 7 to 12 years. Therefore, the teacher used the game learning to attract the students needs and attention. They are natives in their mother tongue (L1) and Bahasa Indonesia as the national language (L2). Furthermore, multilingual education has been implemented in this SDIT concerning its importance and relation to the existing values for future development.Keywords: The role of teachers, multicultural, multilingual education